Automated data analysis in quantitative research: Prototyping an automation software for obtaining fast and reliable insights in quantitative research settings - Wahrenburg, Gero (2023)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management